2021
DOI: 10.1155/2021/6666160
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lncRNA, miRNA, and mRNA Expression Profiling in Type I IFN and Type II IFN Overexpressed in Porcine Alveolar Macrophages

Abstract: Current data is scarce regarding the function of noncoding RNAs (ncRNAs) such as microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) in the interferon- (IFN-) mediated immune response. This is a comprehensive study that analyzes the lncRNA and miRNA expression profiles of the type I IFN and type II IFN in porcine alveolar macrophages using RNA sequencing. There was a total of 152 overexpressed differentially expressed (DE) lncRNAs and 21 DE miRNAs across type I IFN and type II IFN in porcine alveolar macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…In contrast, slightly more novel sRNA/miRNA were detected in the P6 of IFN-w5 treatment (Table 4). More extensive or sRNA/miRNA-specific studies will be needed to test whether this general sRNA differential expression is associated with the respective samples across different treatments (21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, slightly more novel sRNA/miRNA were detected in the P6 of IFN-w5 treatment (Table 4). More extensive or sRNA/miRNA-specific studies will be needed to test whether this general sRNA differential expression is associated with the respective samples across different treatments (21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…Most of our inter-sample RSQ for miRNA expression were larger than 0.97, indicating a critical experiment control across the samples, and shared expression patterns of the miRNA that correlates between the samples. Hence, the minor portion of sampleand miRNA-specific differential expression, which were hypothesized to underlie the observed difference of cellular responses across the samples, were pinpointed for further examination (20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Correlation and Differential Analyses Of Mirna Expression Ac...mentioning
confidence: 99%
See 1 more Smart Citation
“…The top miRNAs with more targets are miR-365-5p, miR-671-5p, miR-885, and miR-205. Studies have shown that miR-365-5p can target RNA-binding protein with serine-rich domain 1 ( RNPS1) , Keratin 14 ( KRT14) , and DnaJ heat shock protein family (Hsp40) member B6 ( DNAJB6) in porcine Alveolar Macrophages, thereby affecting interferon-mediated immune response [ 42 ]. Previous studies have shown that the differentially expressed miR-671-5p in the endometrium of Meishan and Duroc sows affects maternal placental development by targeting the Estrogen Receptor 1 ( ESR1) gene [ 5 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The library was sequenced on the Illumina Hiseq2500 platform by Oebiotech Corporation (Shanghai, China) and 50 bp single-end reads were produced. LncRNA transcriptome and miRNA analysis were performed as per the provided instructions, followed by data analysis as described previously [ 22 ]. LncRNA sequencing data has been submitted to NCBI′s SRA repository under BioProject IDs: PRJNA476718, PRJNA476720, PRJNA476721, PRJNA476722.…”
Section: Methodsmentioning
confidence: 99%